This & object prototypes - Simpson, Kyle (O'Reilly Media, 2014)
No matter how much experience you have with JavaScript, odds are you don't fully understand the language. This concise, in-depth guide takes you inside JavaScript's this structure and object prototypes. You'll learn how they work and why they're integral to behavior delegation - a design pattern in which objects are linked, rather than cloned.